Upaya Membranding Stigma Negatif Tradisi Nikah Sirri di Desa Kalisat, Rembang, Pasuruan Melalui Pelestarian Tradisi Gebluk - Muhammad Khodafi; Hotimah Novitasari (Program Studi Sastra Indonesia UIN Sunan Ampel Surabaya, 2020)
This study aims to (1) Determine the tradition of unregistered marriage and (2) Analyze the positive potential of Gebluk tradition in Kalisat Village as an effort to compare the negative stigma of unregistered marriage. This study uses qualitative research methods based on techniques (1) Literature study, (2) Participant observation and (3) Field studies. This study uses the theory of (1) Historical-Anthropology, (2) Anthony Giddens-Structuration, and (3) Derrida-Deconstruction. The results of this study are that Gebluk tradition is one of the media of Islamization in the village of Kalisat, Rembang, Pasuruan, East Java in the 1960s and is still preserved today. Overall, it can be seen that efforts of branding the negative stigma of the unregistered marriage tradition in Kalisat village are carried out through the preservation of Gebluk tradition through the optimization of the positive potential of both the internal and external pathways.